2020
DOI: 10.15252/embr.201948385
|View full text |Cite
|
Sign up to set email alerts
|

Golgi‐associated microtubules are fast cargo tracks and required for persistent cell migration

Abstract: Microtubules derived from the Golgi (Golgi MTs) have been implicated to play critical roles in persistent cell migration, but the underlying mechanisms remain elusive, partially due to the lack of direct observation of Golgi MT‐dependent vesicular trafficking. Here, using super‐resolution stochastic optical reconstruction microscopy (STORM), we discovered that post‐Golgi cargos are more enriched on Golgi MTs and also surprisingly move much faster than on non‐Golgi MTs. We found that, compared to non‐Golgi MTs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 71 publications
(120 reference statements)
0
31
0
Order By: Relevance
“…MT-dependent transport helps in the delivery of molecules to the leading edge of the cell and to recycle numerous membrane proteins, such as integrins, chemokine receptors or cadherins. These molecules are involved in sensing the microenvironment and controlling FA dynamics and the speed and directionality of migration [127,[159][160][161][162]. Thirdly, the role of IFs in cell migration was initially proposed because of their alterations during cancer invasion and progression.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…MT-dependent transport helps in the delivery of molecules to the leading edge of the cell and to recycle numerous membrane proteins, such as integrins, chemokine receptors or cadherins. These molecules are involved in sensing the microenvironment and controlling FA dynamics and the speed and directionality of migration [127,[159][160][161][162]. Thirdly, the role of IFs in cell migration was initially proposed because of their alterations during cancer invasion and progression.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Golgi28 , lipid droplet, and peroxisome29 .Chretien et al recently reported that mitochondrial temperature reached >323K (50 ℃) using MitoThermo Yellow (MTY) in HEK293T cells treated with an oxygen-rich buffer to fully functionalize the respiration 38 . Intracellular temperature measurement using organic dyes is not suitable for long-term monitoring purpose.…”
mentioning
confidence: 99%
“…The positioning of the Golgi apparatus relative to that of the nucleus has been recognized to associate with the direction of collectively migrating cells (Gomes et al , 2005), while it is evident that the Golgi–nucleus axis is decoupled with cell directionality in random motility (Uetrecht & Bear, 2009). Moreover, our recent opto‐genetic manipulation reveals that turning of the Golgi apparatus lags behind cell steering in single cell migration (Hao et al , 2020). Consistent with the early notion, we observed the front positioning of the Golgi in wound healing assays, where we defined the Golgi–nucleus orientation as the angle between the Golgi–nucleus axis with the wound edge (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%